Implementasi Manajemen Berbasis Sekolah (School- Based Management) dalam Meningkatkan Mutu Pendidikan di MA NW Pepao: Implementation of School-Based Management in Improving the Quality of Education at Madrasah Aliyah NW Pepao - Nasrullah (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2026)
This study aims to determine the implementation of School-Based Management (SBM) in efforts to improve the quality of education at MA NW Pepao and identify the obstacles faced and the strategies taken to overcome them. This study uses a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. Informants in this study consisted of the principal, teachers, the vice principal of curriculum and student affairs, and students. The results show that the implementation of SBM at MA NW Pepao has been carried out in a participatory and gradual manner. The principal acts as a coordinator and facilitator in developing work programs with teachers and the committee. Efforts to overcome obstacles are carried out through collaboration with external institutions, optimization of BOS funds, internal teacher training, and approaching parents through religious activities. Thus, SBM has been proven to be adaptively implemented at MA NW Pepao as a strategy to improve the quality of education.